TAHAPAN PENYESUAIAN LINTAS BUDAYA PADA EKSPATRIAT DI KOTA SEMARANG - Siregar, Reiner Abeltua; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2018)
The past decades of international business research has seen an extraordinary evolution in awareness and understanding of cross-cultural management. In Indonesia, the growth of manpower from various countries, improving environmental performance. Not all expatriates stationed in a new country succeed in their international assignments. This research will analyze which elements can contribute to expatriate cross-cultural adjustment..The purpose of this conceptual research is to present the current literature review related to cross-cultural management. Expatriates adaptation is inevitable in every organization wherever expat is located outside their own country. All adaptation processes are influenced by an internal factor and external factors. Various literature related to this topic is discussed in this study, along with the upcoming research agenda related to cross-cultural management.Â This research uses meta-analysis method by using U-curve hypothesis. Research to represent current literature review related to expatriate cross-cultural adjustment. Various kinds of literature related to the each stages of cross-cultural adaptation according to U-curve are discussed in this study, along with the upcoming research agenda related to change management.